Research data sharing: developing a stakeholder-driven model for journal policies - Sturges, Paul; Bamkin, Marianne; Anders, Jane H.S.; Hubbard, Bill; Hussain, Azhar; Heeley, Melanie (Association for Information Science and Technology, 2014)
The conclusions of research articles generally depend on bodies of data that cannot be included in the articles themselves. The sharing of this data is important for reasons of both transparency and possible reuse. Science, Technology and Medicine journals have an obvious role in facilitating sharing, but how they might do that is not yet clear. The Journal Research Data (JoRD) Project was a JISC (Joint Information Systems Committee) funded feasibility study on the possible shape of a central service on journal research data policies. The objectives of the study included, amongst other considerations: to identify the current state of journal data sharing policies and to investigate the views and practices of stakeholders to data sharing. The project confirmed that a large percentage of journals do not have a policy on data sharing, and that there are inconsistencies between the traceable journal data sharing policies. Such a state leaves authors unsure of whether they should deposit data relating to articles and where and how to share that data. In the absence of a consolidated infrastructure for the easy sharing of data, a journal data sharing model policy was developed. The model policy was developed from comparing the quantitative information gathered from analysing existing journal data policies with qualitative data collected from the stakeholders concerned. This article summarises the information gathered, outlines the process by which the model was developed and presents the model journal data sharing policy in full.